A 2D problem of time-fractional heat order for two-temperature thermoelasticity under hydrostatic initial stress. Issue 4 (12th March 2018) - Sarkar, N.; Lotfy, Kh.
ABSTRACT: The present study solves the problem of thermoelastic interactions in a half-space medium under hydrostatic initial stress in the context of a fractional order heat conduction model with two-temperature theory. The analytical solutions of the field variables are obtained by using the normal mode analysis. The obtained solutions are then applied to a specific problem for a thermally insulated surface which is acted upon by a load. The distributions of the two temperatures, displacements, and the stress components inside the half-space are studied. The graphical results depict that the fractional parameter has significant effects on all the studied field variables. Comparisons are made within the theory in the presence and absence of the hydrostatic initial stress. Thus, we can conclude that the fractional order generalized thermoelasticity model may be an improvement on studying elastic materials.